2010
DOI: 10.1002/app.33163
|View full text |Cite
|
Sign up to set email alerts
|

Probing the dynamics of water in chitosan polymer films by dielectric spectroscopy

Abstract: Chitosan biopolymers are increasingly being used in advanced biomedical applications, where aqueous interactions profoundly influence their physical properties and also their in vivo biomolecular and cellular activity. Here, hydration of chitosan films is studied by dielectric spectroscopy in a conventional constraining plate configuration and compared with free standing films. Film hydration proceeds by an initial water uptake followed by a spontaneous dehydration (deswelling) even in saturated atmospheres. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…The sustained augmentation in the dielectric loss in the low‐frequency range with increasing temperature authenticates the occurrence of Maxwell–Wagner–Sillars (MWS) polarization which results from the separation of charges at the inner dielectric boundary layers . This MWS polarization process has been observed in inhomogeneous materials, such as biopolymers and polysaccharides,including Cs . Both electrode polarization and MWS polarization are of macroscopic nature, directly connected with the DC conductivity of a material, and can mask the dielectric response of a sample in the low‐frequency region.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…The sustained augmentation in the dielectric loss in the low‐frequency range with increasing temperature authenticates the occurrence of Maxwell–Wagner–Sillars (MWS) polarization which results from the separation of charges at the inner dielectric boundary layers . This MWS polarization process has been observed in inhomogeneous materials, such as biopolymers and polysaccharides,including Cs . Both electrode polarization and MWS polarization are of macroscopic nature, directly connected with the DC conductivity of a material, and can mask the dielectric response of a sample in the low‐frequency region.…”
Section: Resultsmentioning
confidence: 74%
“…43 This MWS polarization process has been observed in inhomogeneous materials, such as biopolymers and polysaccharides, 82,84 including Cs. 34,38,85,86 Both electrode polarization and MWS polarization are of macroscopic nature, directly connected with the DC conductivity of a material, and can mask the dielectric response of a sample in the low-frequency region.…”
Section: Molecular Dynamicsmentioning
confidence: 99%
“…Dielectric spectroscopic measurements were made on the free standing films which were provided with silver epoxy electrodes (10 × 10 mm 2 ) and multistrand copper wire leads in a condenser mode configuration since we have previously shown that conventional parallel plate configurations, which constrain the biopolymer film during hydration, influenced their dielectric response 23. Data was collected over the frequency range 10 1 –10 6 Hz to probe the water induced relaxation behavior of these samples using a HP 4192A low frequency impedance analyzer (Hewlett‐Packard) on samples within a chamber under controlled relative humidity conditions at a constant temperature of 300 K. The signal amplitude was maintained at 1 V rms throughout the measurements, providing an accuracy of measured capacitance ±0.01 pF for low water content samples and ±1 pF for high water contents.…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, the dielectric loss, ε″ was corrected for conductivity. The procedure adopted for simultaneous measurement of water uptake and dielectric properties of the chitosan films has been detailed previously 23…”
Section: Methodsmentioning
confidence: 99%
“…The relative permittivity of chitosan is approximately 5.0, that of poly‐HEMA is about 9.0 and that of polystyrene about 2.2 (similar to that of benzene or toluene). From these static permittivities, the above change in selectivity is well explained by the change in the sign of the reaction field.…”
Section: Resultsmentioning
confidence: 95%